Capitalism's inflation and unemployment crisis : beyond Monetarism and Keynesianism - Weintraub, Sidney (Reading, Mass. : Addison-Wesley, 1978)
This book takes a fresh look at the topic of paramount economic concern: stagflation. The book surveys the major approaches to analyzing and explaining the simultaneous ills of inflation and unemployment plaguing the market economies and presents in some detail the author's innovative income-gearing proposals for achieving a stable economic order.
Includes bibliographical references and index.
rpm 07/11/2017
Loans
Keywords: Unemployment; Wage-price policy; Keynesian economics; Chicago school of economics